Expression Analysis of SR-B1 Gene in Type-2 Diabetes Mellitus Patients with and Without Dyslipidemia (Medical Forum Monthly, 2021)
Objective: To perform expression analysis of the SCARB1 gene to find out the association of High-density lipoprotein cholesterol (HDL-C) level with SR-B1 receptor expression in patients of type 2 diabetes mellitusStudy Design: A cross sectional comparative studyPlace and Duration of Study: This study was conducted at the department of Biochemistry, Quaid e Azam Medical College, Bahawalpur from January, 2020 to June, 2020.Materials and Methods: A total of 60 subjects of both genders aged 18 to 70 years were enrolled. Group-A (n=20) comprised of patients who had type 2 diabetes with dyslipidemia, Group-B (n=20) as type 2 diabetes without dyslipidemia while Group-C (n=20) was control (without diabetes and having normal lipid profile). PCR conditions optimized and quantitative real time PCR performed using SYBER Green fluorescence dye kit. Comparative ΔΔCT method applied to quantify the SCARB1 gene expression in control and disease groups.Results: In a total of 60 subjects, there were 34 (56.7%) male and 26 (43.3%) female. Overall, mean age was recorded to be 48.24+6.77 years. ΔΔCT discovered the reduction in SCARB1gene expression in Group-A in comparison to Group-B and Group-C.Difference in expression of target gene was noted to be 1-fold in comparison to other groups. Mean values were found to have significant differences among Ct of Group-A (26.47±6.21), Group-B (18.69±3.76) and Group-C (19.78±5.25). Raised Ct value in Group-A reviewed abundance of target gene transcript with less copy number and found to have alterations in SR-B1 receptor which could be the cause of derangement in lipid profile in type 2 diabetes.Conclusion: Hyperglycemia inhibits the expression of SCRB1 gene. Hyperglycemia might be responsible for reverse cholesterol transport by controlling SR-BI expression in diabetic patients resulting in the atherosclerotic changes and increasing the incidents of cardiovascular complications.